ATYPCAL INFECTION IN CHILDREN - Pikul E, V. (World of Medicine and Biology, 2014)
In the thesе presents an analysis based literature data, the causes and clinical manifestations of the various forms of atypical infections in children. In a world infected with up to 1 billion. People and every year new patients for chlamydia record 4 million аnd 100000 children with symptomatic forms of the disease, 15% of stillbirths, perinatal mortality rate - 35%. Mycoplasmosis in 77,3% of cases seen with other infections - chlamydia, virus, etc. Legionellosis today called the disease of industrialization.Chlamydia - a gram-negative microorganisms grupa that take place between viruses and bacteria. Mycoplasma infection treat class Mollicules and also on the structure stands on the middle between viruses, bacteria and protozoa. These microorganisms have RNA and DNA. Legionella pneumophila - Gram-negative pathogen, which allocates endotoхin and eхotoхin. Bol is open 40 species of Legionella from them 22 species include 35 serovars that are pathogenic to humans.In particular, the author paid much attention chlamydiоsis, mycoplasmosis and legionellosis as one of the atypical manifestations of infection in childhood.The pathogenesis of Chlamydia are destroying epithelial host cells, the occurrence of hemodynamic disturbances and destruction of chlamydia in cells, L-transformation and persistence. Respiratory Chlamydia in infants under 6 months of often develops on the background or after suffering conjunctivitis. Typically no data on contact with SARS patients. Most often diagnosed pneumonia, accompanied by bronchial obstruction. The first signs after intrapartum infection may be from 5 days to several months. Late of disease caused by subclinical course and activation under the influence of various factors.Features pathogenesis: mycoplasmosis is damage epithelial cells of the respiratory tract, including the process involved alveoli, leading to interstitial pneumonia. In severe cases, possible hematogenous dissemination of drift to other organs and development clinics hepatitis, meningitis, nephritis.Features Legionellosis pathogenesis is destruction agent terminal bronchioles and alveoli. Pulmonary infiltrate consisting of leukocytes, fibrin, alveolar cells, then can cause infectious-toxic shock and destruction of others. There are three forms Legionellosis: pneumonic, fever Pontiac and fever Fort Bragg. The incubation period of 2-10 days. Respiratory form has the following clinical picture: acute onset of febrile, dry cough and chest pain, then turns into productive cough with bloody sputum.In the treatment of atypical infections as etiotropnoy therapy used macrolides.
Keywords: children; atypical infection; treatment